The Influence of Parental Support and Spiritual Intelligence on Self Regulated Learning of SMAIT Hidayah Klaten Students - Armasyahdanti, Keysha Firdausy; Khilmiyah, Akif (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to analyze the influence of parental support and spiritual intelligence on the Self-Regulated Learning (SRL) ability of SMAIT Hidayah Klaten students. The research method uses a quantitative approach with data collection techniques through questionnaires filled out by 155 students selected by purposive sampling. The results of multiple linear regression analysis showed that parental support and spiritual intelligence simultaneously had a significant effect on SRL (F count = 62.367; p = 0.000), with a contribution of 45.1%. Partially, both variables also exerted a significant positive influence (parental support: t = 5.240; p = 0.000; spiritual intelligence: t = 5.459; p = 0.000). These findings indicate that a supportive family environment and the development of spiritual intelligence can increase students' independence in managing learning and form more responsible characters. The implications of this study emphasize the importance of collaboration between schools and parents and the integration of spiritual values in the curriculum to optimize students' SRL. This study makes an important contribution to the development of a holistic learning model in faith-based schools.